Gebühren für die Nutzung der Straßeninfrastruktur - Eine Abwägung. - Maier, Friedrich; Busch, Fritz (Kirschbaum, 2011)
Gebühren für die Nutzung der Straßeninfrastruktur werden immer wieder kontrovers diskutiert, genährt durch die hohe Verkehrsnachfrage mit ihren verzweigten Wirkungen, die Begrenzung des Verkehrsaufgebots durch die Infrastruktur und die Knappheit der Mittel für ihren Betrieb, ihre Instandhaltung und ihren Ausbau. Ziele einer Gebührenerhebung können die Generierung von Einnahmen oder die Beeinflussung der Verkehrsnachfrage sein. Der Beitrag beschreibt die bisherigen Abgaben der Straßenverkehrsteilnehmer in Deutschland sowie die Grundlagen hinsichtlich Rechtslage, Technologien und Gebührenordnung, nimmt Bezug auf den Diskurs um die Auslastung externer Kosten in Internationales Verkehrswesen aus den Jahren 2008 bis 2009 und diskutiert Erfahrungen mit internationalen städtischen Anwendungen und mit der LKW-Maut in Deutschland.

Existing traffic charges suffice for investments for the German road network and its operation. These charges already offer incentives to road users to buy economic cars and to reconsider their driving behaviour. Nevertheless good reasons exist to charge heavy vehicles due to the far-above-average road damages they cause. The article discusses the legal framework for road pricing (RP) and reviews RP applications. The complete reinvestment of revenues into transport projects is considered as implausible. The charging of external traffic costs is examined: If road traffic was additionally charged for pollution and noise, other emitters should be included as well. Accident expenses are covered by insurance except for long term costs of injuries and fatalities, which are highest on rural roads (per km). However, it is for this road category that charges are discussed the less. Delay is caused and experienced by motorists; therefore it should not be charged. Nevertheless, RP can cause a more economic infrastructure use in the case of spatio-temporally differentiated charging schemes focused on positive traffic effects but not on maximising revenues.
Road Pricing - An Assessment.
Keywords: Verkehr; Verkehrsinfrastruktur; Individualverkehr; Infrastrukturinvestition; Nutzwertanalyse; Finanzierungsmodell; Gebühr; Verkehrsteuer; Straßenbenutzungsgebühr